Making history for God essays on evangelicalism, revival and mission : a tribute to Stuart Piggin, Master of Robert Menzies College, 1990-2004 - Treloar, Geoffrey Robert; Linder, Robert D. (Sydney, NSW Robert Menzies College, 2004)
Contents : The vision of the evangelical historian ; Seeing Australian churches ; Seeing Australian Christianity; Seeing all the world.
Includes: "Out of all proportion": Christian Brethren influence in Australian Evangelicalism, 1850-1990 / Margaret Yarwood Lamb. Other contributors include David W. Bebbington, Edwin A. Judge, Mark Noll, Ian Breward, Mark Hutchinson, et.al.
Keywords: Piggin, Stuart; Evangelicalism -- Australia -- history; Church history -- Australia